2021
DOI: 10.1007/s10775-021-09473-4
|View full text |Cite
|
Sign up to set email alerts
|

Career/lifelong guidance systems and services: continuous transformations in a transition region

Abstract: This comparative study traces the foundation and development of vocational and career guidance services in three Central and Eastern European countries in the light of the contextually bound factors of this region. Since the beginning of the 20th century, political transitions and changes in the ruling structures in these countries were so frequent that the same generation was often confronted with multiple forms of governance: the rule of 'König und Kaiser', the monarchy, the communist regime, neoliberal econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…e college student employment guidance system has helped many graduates find suitable jobs. e results of a report point out that career guidance for graduates needs to evolve with the times while suggesting that major universities should set up their own career guidance agencies to be responsible for career guidance services for college graduates [4,5]. is report also describes how the basic framework of a career guidance system in UK universities should include key elements such as counseling services, advice information, contacting employers, and arranging job interviews.…”
Section: Introductionmentioning
confidence: 99%
“…e college student employment guidance system has helped many graduates find suitable jobs. e results of a report point out that career guidance for graduates needs to evolve with the times while suggesting that major universities should set up their own career guidance agencies to be responsible for career guidance services for college graduates [4,5]. is report also describes how the basic framework of a career guidance system in UK universities should include key elements such as counseling services, advice information, contacting employers, and arranging job interviews.…”
Section: Introductionmentioning
confidence: 99%
“…By the time COVID struck, Hungary had had a century-long tradition of career guidance services (Borbély-Pecze et al, 2021) and a history of nearly two decades of national strategy-writing for the digitisation of public services. However, the pandemic and the resulting lockdown period in Hungary disrupted the functioning of traditionally face-to-face counselling models, and the challenges pointed to a divide between the vision formulated in digitalisation strategies and the reality of daily practice.…”
Section: Abstraktimentioning
confidence: 99%
“…The results showed that planned behavior can provide a positive outlook on the career development of urban and rural students (Haque et al, 2017). Comparative studies in several European countries show that career guidance has to adjust its methods because a country is bound to experience changes in rules that are integrated with cultural values (Aróstegui, 2022;Borbély-Pecze et al, 2022).…”
Section: Introductionmentioning
confidence: 99%